2018
DOI: 10.13057/biodiv/d190104
|View full text |Cite
|
Sign up to set email alerts
|

Tree standing dynamics after 30 years in a secondary forest of Bali, Indonesia

Abstract: Siregar M, Undaharta NKE. 2018. Tree standing dynamics after 30 years in a secondary forest of Bali, Indonesia. Biodiversitas 19: 22-30. Tree standing dynamics in 0.5 ha plot after 30 years in Bukit Tapak secondary forests, Batukahu Nature Reserve, Province 0f Bali was studied by using plot method. The results showed that the tree species richness is same, 33 species, but there are six species disappear and be replaced by another species as a newcomer. Eight species persist as major species based on the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(21 reference statements)
2
2
0
2
Order By: Relevance
“…The existence of cultivated plant (Coffea arabica and Citrus hystrix) and domination of pioneer plants in site one, including Homalanthus populneus, Macaranga tanarius, Mallotus sphaerocarpus and Ficus spp. also confirmed that two plots were located in secondary forest (Siregar & Undaharta, 2018;Zuhri & Mutaqien, 2013) . Disturbed forest formed gaps that caused high penetration of sunlight affecting the growth of pioneer species (Mutaqien & Zuhri, 2011;Purwaningsih et al, 2017) .…”
Section: Species Composition and Succession Statussupporting
confidence: 68%
See 1 more Smart Citation
“…The existence of cultivated plant (Coffea arabica and Citrus hystrix) and domination of pioneer plants in site one, including Homalanthus populneus, Macaranga tanarius, Mallotus sphaerocarpus and Ficus spp. also confirmed that two plots were located in secondary forest (Siregar & Undaharta, 2018;Zuhri & Mutaqien, 2013) . Disturbed forest formed gaps that caused high penetration of sunlight affecting the growth of pioneer species (Mutaqien & Zuhri, 2011;Purwaningsih et al, 2017) .…”
Section: Species Composition and Succession Statussupporting
confidence: 68%
“…Tilu, West Java. Domination of Moraceae and Euphorbiaceae were characteristic of secondary forest and most of the dominated tree families characterize the mountain ecosystem (Laumonier, 1997;Siregar & Undaharta, 2018) .…”
Section: Species Composition and Succession Statusmentioning
confidence: 99%
“…First, some tree species have important economic value which makes them under pressure due to over-exploitation, leaving them vulnerable to population extinction in their natural habitat (Budiharta et al 2011). Second, information about tree structure can provide insight on regenerative ability of the stand in a forest area, both in present time and in the future (Laumonier et al 2010;Mongabay 2013;Prawiroatmodjo and Kartawinata 2014;Ifo et al 2016;de Carvalho et al 2017;Henry et al 2017;Manral et al 2018;Siregar and Undaharta 2018;Salvana et al 2019). Third, tree community is the largest contributor of above-ground biomass in tropical forests (Slik et al 2010;Feldpausch et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kawasan ini berada di daerah pegunungan dengan ketinggian 1250-1400 m dpl., kisaran suhu udara antara 14-22,5 o C, kelembaban udara 70-96%, intensitas cahaya matahari 45-60%, dan curah hujan 2000-3000 mm/tahun (Putri, 2018; https://krbali.lipi.go.id/sejarah.html). Kondisi area observasi berada di bawah tegakan tanaman reboisasi rasamala, Altingia excelsa Noronha (Altingiaceae) hasil penanaman tahun 1958 (Siregar & Undaharta, 2014), yang berfungsi sebagai batas area sekaligus zona penyangga hutan alam CA Batukaru (Siregar & Undaharta, 2018). Area ini dipenuhi dengan seresah yang didominasi oleh dedaunan kering A. excelsa, dengan tebal lebih kurang 5-10 cm.…”
Section: Tempat Penelitianunclassified